Reaching across the waters : facing the risks of cooperation in international waters - Subramanian, Ashok, 1950- (Directions in development (Washington, D.C.). Environment and sustainable development., 2012)
This volume reviews the experience of cooperation in five international river basins, focusing on the perceptions of risks and opportunities by decision makers in countries responding to a specific prospect of cooperation. For each basin, the analysis centered on "tipping points," or periods in time when policymakers in the countries involved were faced with a critical decision concerning water cooperation. This study was inspired, in part, by the intensified involvement of the World Bank and development partners in shared international waters, resulting in a growing interest to better underst.